2017
DOI: 10.1007/164_2016_118
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Physiology and Function

Abstract: The gastrointestinal (GI) system is responsible for the digestion and absorption of ingested food and liquids. Due to the complexity of the GI tract and the substantial volume of material that could be covered under the scope of GI physiology, this chapter briefly reviews the overall function of the GI tract, and discusses the major factors affecting GI physiology and function, including the intestinal microbiota, chronic stress, inflammation, and aging with a focus on the neural regulation of the GI tract and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(101 citation statements)
references
References 41 publications
1
82
0
1
Order By: Relevance
“…Numerous pathologies that link inflammation, gut microbiota and ENS have been described ( Greenwood-Van Meerveld et al, 2017 ). Along those lines, recent data have shown that specific neurodegenerative diseases (i.e., multiple sclerosis, Parkinson disease) were also characterized by gastrointestinal comorbidities.…”
Section: Gut-brain Axis and Type 2 Diabetesmentioning
confidence: 99%
“…Numerous pathologies that link inflammation, gut microbiota and ENS have been described ( Greenwood-Van Meerveld et al, 2017 ). Along those lines, recent data have shown that specific neurodegenerative diseases (i.e., multiple sclerosis, Parkinson disease) were also characterized by gastrointestinal comorbidities.…”
Section: Gut-brain Axis and Type 2 Diabetesmentioning
confidence: 99%
“…Colonic mucosal biopsies from young and old non-human primates (baboons) demonstrate significant differences in permeability and TJ proteins. The older baboons displayed a significant decrease in ZO-1, occludin, and JAM-A proteins, and an increase in claudin-2 expression, all of which correlated with increased permeability in the old aged group [66]. Another study in monkeys found that old monkeys have an increase in FITC dextran flux compared to young monkeys [67].…”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 99%
“…Specifically, the strongest link between gut permeability and bone loss comes from colitis studies where barrier disruption in adult animal models leads to bone loss, even without weight loss [84][85][62]. Thus, as animals and humans age, intestinal permeability increases [64][65][66][67][62][69] and could contributes to age-related bone loss. In addition, increased permeability likely promotes the low-grade chronic inflammation, termed “inflammageing” [72][67][75], and many studies link low grade inflammation with bone loss [84][85][62].…”
Section: Barrier Pathophysiology In Developmentmentioning
confidence: 99%
“…The permeability of these pathways is typically measured using several complementary methods. TEER measures the net flux of all ions (cations and anions) across the epithelium (pore and leak pathway) 22 . The most common ions in physiological solutions, Na + and Cl − , carry this current.…”
Section: Discussionmentioning
confidence: 99%